Improving Student Career Planning Through Information Services Using Career Card Media - Miswanto, Miswanto; Sitio, Dio Alpian; Muna, Hanifatul; Andriyani, Rizka; Pratiwi, Sekar Ayu; Simbolon, Syakira Nazla (CV. Rayyan Dwi Bharata, 2025)
Career planning is an important thing that can help students understand themselves better and gain a better understanding of career information. In determining a career, students need information about careers to use as alternatives that suit their interests and talents. This research is based on students' lack of understanding about careers, causing students to often experience confusion in choosing a career. Career cards are a fun and interactive medium that can increase students' understanding of careers. These career cards are considered a promising approach to enhance career planning in a fun and effective way. The method used in this research is RD development research where researchers develop a product and produce new products and test them. The research subjects were high school students with data collection techniques using questionnaires.